Registry of Randomized Criminal Justice Experiments in Sanctions, 1951-1983 - Weisburd, David ([Verlag nicht ermittelbar], 1992)
This registry categorizes, summarizes, and analyzes datasets containing information on randomized criminal justice experiments in sanctions. These datasets vary in methodology, geographic region, and other aspects. Among the topics covered in this registry are the nature of offense being sanctioned, type of sanction, racial and sexual composition of the sample, and procedures and outcomes of each collection.